Can selective withdrawal control algal blooms in reservoirs? The underlying hydrodynamic mechanism. (25th March 2023) - Song, Yang; Chen, Min; Li, Jia; Zhang, Linglei; Deng, Yun; Chen, Jichang
Abstract: Selective withdrawal is considered an effective and convenient method to mitigate thermal pollution and environmental problems in reservoirs and downstream rivers. However, the potential effects of selective withdrawal on harmful algal blooms in reservoirs remain uncertain, threatening sustainable reservoir management. This study developed and calibrated a three-dimensional (3D) hydro-ecological model for the Zipingpu reservoir to numerically investigate how selective withdrawal scenarios (including surface, middle, and bottom withdrawal) affect algal growth and hydrodynamic environments. The surface withdrawal scenario could inhibit algal growth efficiently, causing Chlorophyll a (Chl a) concentration below 10 μg L −1  consistently. The Chl a concentration decreased from 27.0 μg L −1 for bottom withdrawal and 21.2 μg L −1 for middle withdrawal to 3.3 μg L −1 for surface withdrawal in the bloom period. The nutrient, light, and temperature limitations among the three withdrawal scenarios showed slight differences and were not the main reason for the bloom differences. Compared with the bottom and middle withdrawal scenarios, the surface withdrawal scenario weakened stratification and decreased surface water temperature, suggesting inhibitory effects on algal blooms. The bottom and middle withdrawal scenarios significantly reduced surface flow velocity and made the flow direction against the water intake, indicating a favorable hydrodynamic environment for algal growth. The surface withdrawal scenario reduced hydraulic residence time, thereby restraining algal growth and accumulation in the reservoir. Implementing surface withdrawal might be an efficient and promising method to prevent algal blooms in reservoirs. These results not only highlight the potential of selective withdrawal for algal bloom control but also reveal that accelerating surface flow velocity is the key mechanism. Graphical abstract: Image 1 Highlights: Surface withdrawal creates unfavorable hydrodynamic conditions for algal growth. Surface withdrawal can decrease Chl a concentration below 10 μg L −1 . Bottom and middle withdrawal probably promote algal blooms. Selective withdrawal has the potential to mitigate eutrophication in reservoirs.